Assessment of museum staff exposure to arsenic while handling contaminated exhibits by urinalysis of arsenic species - Mithander, Amanda; Göen, Thomas; Felding, Gitte; Jacobsen, Peter (Journal of Occupational Medicine and Toxicology, 2017)
Preservation of museum objects with inorganic arsenic compounds and contamination of the surroundings has previously been documented. The present study addresses the exposure of museum staff by measuring arsenicals in urine. After 1 week without exposure, urinary samples were taken before and after handling of preserved skins and analysed by HPLC-ICP-MS for inorganic arsenic, arsenic metabolites and arsenobetaine. The sum of inorganic arsenic and metabolites was an index of exposure. Information about work and seafood intake was obtained by questionnaire. One out of five subjects had a work-related rise in the exposure index of 18.1 ?g As/L to a post-exposure level of 37.1 ?g As/L. Four subjects had no certain exposure-related increase in the index. The study indicates that museum staff may be exposed to arsenic from handling arsenic-preserved objects and supports the use of specified arsenic analysis to avoid interference from organic arsenic.
EVALuna2:9771